ChemInform Abstract: Copper(II)/Silver(I)‐Catalyzed Sequential Alkynylation and Annulation of Aliphatic Amides with Alkynyl Carboxylic Acids: Efficient Synthesis of Pyrrolidones. Issue 29 (June 2016) - Zhang, Jitan; Li, Danyang; Chen, Hui; Wang, Binjie; Liu, Zhanxiang; Zhang, Yuhong
Abstract: This copper‐catalyzed tandem decarboxylative cross‐coupling/cyclization provides a highly efficient method for preparation of pyrrolidones.